Henry S. R. Kao y Runjahn Hoosain (comp.). Linguistics, Psychology, and the Chinese Language. Centre of Asian Studies, University of Hong Kong, 1986, 333 pp. - Maeth Ch., Russell (Estudios de Asia y África, 1991)
-